1999
DOI: 10.1046/j.1464-5491.1999.00187.x
|View full text |Cite
|
Sign up to set email alerts
|

High impact of nephropathy on five‐year mortality rates among patients with Type 2 diabetes mellitus from a multi‐ethnic population in New Zealand

Abstract: Maori with Type 2 diabetes are dying from diabetic complications, particularly nephropathy, at an alarming rate. The magnitude of the difference between Maori and Pacific Islands Polynesians suggests environmental rather than inherited factors are involved and these need further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…Compared with New Zealanders of European descent (‘Europeans’), Maori and Pacific people experience high rates of gestational diabetes [7], known diabetes [6] and undiagnosed diabetes [8]. Maori and Pacific people with diabetes have high mortality rates [9] and rates of nephropathy [10], and other complications [11]. Self‐reported rates of cataract, blindness and past photocoagulation are higher in the Maori and Pacific populations than in Europeans [12].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with New Zealanders of European descent (‘Europeans’), Maori and Pacific people experience high rates of gestational diabetes [7], known diabetes [6] and undiagnosed diabetes [8]. Maori and Pacific people with diabetes have high mortality rates [9] and rates of nephropathy [10], and other complications [11]. Self‐reported rates of cataract, blindness and past photocoagulation are higher in the Maori and Pacific populations than in Europeans [12].…”
Section: Introductionmentioning
confidence: 99%
“…Maoris with type 2 diabetes are 15 times more likely to die from diabetic nephropathy than NZ Europeans with type 2 diabetes [2]. Incidence rates and hazard ratios for end-stage renal disease (ESRD) among Maori diabetes patients have not been estimated previously.…”
Section: Introductionmentioning
confidence: 99%
“…Simmons et al . [1] found that 24.8% of middle‐aged New Zealand (NZ) Maori (average age 55 years) with known diabetes had died within 5 years. One explanation for this relatively low survival of Maori into old age may be the early presentation of Type 2 diabetes in combination with an increased incidence of nephropathy in Maori.…”
mentioning
confidence: 99%
“…If, as Simmons et al . [1] suggest, environmental factors are involved in the high impact of nephropathy on Maori mortality rates, then factors other than these environmental factors must therefore play a role. The challenge now is to continue the search for genetic and other factors in addition to modifying established risk factors if we are to reduce the alarmingly high incidence of diabetic nephropathy and end‐stage renal failure in our middle‐aged NZ Maori population.…”
mentioning
confidence: 99%